Investigating The Challenges of Teaching and Learning Writing Skills in The Algerian Primary Schools. The Case of Fifth Grade (About Mohammed Akli- Semmache) In Bouira. - CHABI, Naouel (University of Akli Mouhand Oulhadj, Bouira, 2025)
In response to English’s growing global dominance in media, business, and international communication, Algeria has introduced English as a second foreign language in primary schools, starting from the third grade. While this reform reflects the country's recognition of English’s importance, it poses significant challenges in Algeria’s multilingual context, where Arabic and Tamazight are official languages and French remains the dominant foreign language. This study investigates the difficulties faced by fifth-grade learners and teachers in developing and teaching English writing skills, focusing on Abbout Mohamed Akli, Semmache Primary School in Bouira. Using a mixed-methods approach teacher interviews and student questionnaires the research explores educational, linguistic, and cultural barriers that hinder writing proficiency. The study addresses four key questions: What challenges do teachers face in teaching writing? What difficulties do learners encounter in acquiring writing skills? What strategies can teachers use to address these challenges? And how can learners improve their writing abilities? The research hypothesizes that limited resources, inadequate teacher training, and minimal exposure to English outside the classroom hinder writing instruction. It also suggests that curriculum constraints, the simultaneous learning of French and English, and time limitations negatively affect learners’ writing development. Findings reveal that students struggle with vocabulary, grammar, organization, and confidence, while teachers report insufficient training, time, and support. The study emphasizes the need for student-centered, interactive teaching, better teacher preparation, and curriculum reform. It concludes with practical recommendations aimed at enhancing writing instruction and supporting the success of Algeria’s recent educational reforms.
Writing Skills, Primary Education, Teacher Challenges, Student Difficulties
Keywords: Writing Skills, Primary Education, Teacher Challenges, Student Difficulties